Cerebellar Liponeurocytoma Mimicking Medulloblastoma: Case Report of a Childhood and Literature Review - Dong, Changhui; Jiang, Yining; Zhao, Liyan; Wang, Yubo; Bai, Yang; Sun, Ying; Li, Yunqian (Frontiers in Oncology, 2021)
ABSTRACT Background: Cerebellar liponeurocytoma is a rare benign neoplasm of the central nervous system, which arises mainly in adult patients with only 3 cases reported in children. Due to its rarity, the diagnosis and treatment strategies for cerebellar liponeurocytoma remain unclear. The purpose of this study was to explore the epidemiology, clinical features, imaging findings, pathological characteristics, different diagnoses, treatment, and prognosis of cerebellar liponeurocytoma in juveniles. Case description: A 5-year-old boy was admitted to the department of neurosurgery due to a 5-month history of headaches, nausea, vomiting, dizziness, dysphoria, as well as visual blurring associated with the peak of the headache. Magnetic resonance imaging showed a 4.9×5.4×6.2 cm mass located in the fourth ventricle and cerebellar vermis combined with hydrocephalus and periventricular edema. The mass was completely removed and pathological examination indicated a cerebellar liponeurocytoma of the World Health Organization Grade II classification. Conclusion: The present study was the first to report a cerebellar liponeurocytoma with total tumor resection and adjuvant radiotherapy in a pediatric patient. Total tumor resection and postoperative radiotherapy together with close and long-term follow-up seem to be the optimal treatment strategy for juvenile patients. However, the side-effect of radiation needs to be considered.